Automated Measurements of Atmospheric Aerosols and Black Carbon on Commercial Cruise Voyages with the Portable Atmospheric Measurement box On Sea (PAMOS): MS Fridtjof Nansen from November 2024 to March 2025 - Laura Köhler; Andreas Herber (PANGAEA, 2025)
The Portable Atmospheric Measurement box On Sea (PAMOS) is a fully automated instrument designed for air monitoring on commercial vessels, requiring no maintenance from the crew. First prototypes were deployed on the MS Fridtjof Nansen, a cruise ship operated by HX, in 2024. PAMOS unit 002 was installed on the MS Fridtjof Nansen for the Antarctic season and collected data south of 60°S on eleven round trips between Ushuaia and the Antarctic Peninsula from 30 November 2024 to 26 March 2025. The datasets include GPS positions (from both PAMOS and the vessel extquotesingles navigation system when available), meteorological parameters (air temperature, pressure, relative humidity, relative wind speed and direction, and precipitation measured with a Vaisala WXT536), aerosol properties (particle number concentration from a naneos Partector 2, black carbon from a MA350, and particulate matter from an OPC-R2), and trace gases (CO?, CO, CH?, SO? from smartgas sensors). Quality flags are provided for all parameter groups and should be considered when using the data.